Anode protection film and battery
Patent Information
- Application Number
- JP2023140048
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0018】 本発明の一態様によれば、デンドライトの発生を抑制し、イオン伝導性及びクーロン効率が向上した負極保護膜、並びに、当該負極保護膜を含む電池が提供できる。
Smart Images

Figure 2025033965000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode protective film and a battery. [Background technology]
[0002] As one of high-performance batteries, secondary batteries using lithium ions or the like have been attracting attention. A secondary battery using lithium ions or the like includes, for example, a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode. Various materials used for the secondary battery have been studied.
[0003] Patent Document 1 discloses a binder composition for lithium ion secondary battery electrodes, which contains a copolymer X and a solvent. The copolymer X is obtained by polymerizing a monomer composition X, which contains an ethylenically unsaturated carboxylic acid compound (A) and a copolymerizable compound (B) having an ethylenically unsaturated bond. The ethylenically unsaturated carboxylic acid compound (A) is composed of at least one of an ethylenically unsaturated carboxylic acid and a salt thereof, and the compound (B) has a solubility of 7 g or more in 100 g of water at 20° C. The monomer composition X has a ratio of the ethylenically unsaturated carboxylic acid compound (A) in the total monomers of 20.0 mass % or more and 75.0 mass % or less, a ratio of the compound (B) in the total monomers of 20.0 mass % or more and 75.0 mass % or less, and the electrolyte swelling degree of the copolymer X is less than 120%.
[0004] Patent Document 2 discloses a lithium metal battery including a positive electrode, a lithium negative electrode, and an electrolyte solution interposed therebetween, and including a protective film disposed on at least a portion of the lithium negative electrode, the protective film including one or more first polymers selected from polyvinyl alcohol and polyvinyl alcohol blends. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-123590 A [Patent Document 2] JP 2016-219411 A Summary of the Invention [Problem to be solved by the invention]
[0006] The copolymer X disclosed in Patent Document 1 is a binder composition for lithium ion secondary battery electrodes, and is not a copolymer used for forming a negative electrode protective film.
[0007] The protective film disclosed in Patent Document 2 is formed by directly coating lithium metal with a protective film containing polyvinyl alcohol. Since metallic lithium reacts with moisture in the air, all steps for forming the protective film are performed in a dry environment. For this reason, the steps for forming the protective film disclosed in Patent Document 2 are complicated.
[0008] However, there is a demand for further improvement in the performance of lithium ion secondary batteries. When, for example, a lithium negative electrode is used as the negative electrode of a lithium ion secondary battery, it is possible to increase the energy density of the battery. However, when a lithium negative electrode is used as the negative electrode, dendrites may be formed on the surface of the lithium negative electrode. When dendrites are formed on the surface of the lithium negative electrode and grow, a short circuit may eventually occur in the lithium ion secondary battery. For this reason, there is a demand for further improvement in the protective layer for protecting the negative electrode.
[0009] An object of the present invention is to provide an anode protective film that suppresses the generation of dendrites and has improved ionic conductivity and Coulombic efficiency, and a battery including the anode protective film. [Means for solving the problem]
[0010] [1] A negative electrode protective film that covers at least a portion of a negative electrode, The present invention includes an alkylene oxide copolymer including a structural unit derived from an alkylene oxide and a structural unit derived from an epoxide having a crosslinkable functional group, The alkylene oxide-derived structural unit includes a propylene oxide-derived structural unit, The alkylene oxide copolymer contains 70.0 mol % or more of the propylene oxide-derived structural units relative to the entire alkylene oxide copolymer, the epoxide-derived structural unit having a crosslinkable functional group is a structural unit derived from at least one selected from the group consisting of allyl glycidyl ether, glycidyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate glycidyl ether, and is contained in an amount of 0.3 mol % or more and 20.0 mol % or less with respect to the entire alkylene oxide copolymer; Negative electrode protective film.
[0011] [2] The negative electrode protective film according to [1], the alkylene oxide-derived structural unit is the propylene oxide-derived structural unit, The propylene oxide-derived structural unit is a structural unit represented by the following structural formula (A1): The epoxide-derived structural unit having a crosslinkable functional group is at least one structural unit selected from the group consisting of structural units represented by the following structural formula (B1), structural formula (B2), structural formula (B3), and structural formula (B4): Negative electrode protective film.
[0012] [ka]
[0013] [ka]
[0014] [3] The anode protective film according to [1] or [2], the amount of the alkylene oxide copolymer eluted in ethyl acetate is 10% or less; The degree of swelling of the alkylene oxide copolymer in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 50% or more and 200% or less. Negative electrode protective film.
[0015] [4] The anode protective film according to any one of [1] to [3], the negative electrode protective film further contains an electrolyte, the electrolyte solution contains a carbonate-based solvent and a lithium salt; a molar ratio of the lithium salt to the carbonate-based solvent (the lithium salt / the carbonate-based solvent) is 1 / 6 or more and 1 / 1 or less; Negative electrode protective film.
[0016] [5] The anode protective film according to any one of [1] to [4], The negative electrode is a lithium negative electrode. Negative electrode protective film.
[0017] [6] The negative electrode protective film according to any one of [1] to [5], battery. Effect of the Invention
[0018] According to one aspect of the present invention, it is possible to provide an anode protective film that suppresses the generation of dendrites and has improved ionic conductivity and Coulombic efficiency, and a battery including the anode protective film. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a cross-sectional view that illustrates an example in which the negative electrode protective film according to the present embodiment is used. [Diagram 2] 1 is a cross-sectional view illustrating an example of a main part of a battery according to an embodiment of the present invention. [Figure 3A] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 1. [Figure 3B] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 2. [Figure 3C] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 3. [Figure 3D] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 4. [Figure 3E] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 5. [Figure 3F] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 6. [Figure 3G] 1 is a chart showing the results of 1H-NMR measurement of the copolymer synthesized in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described below by taking an embodiment as an example, but the present invention is not limited to the content of the embodiment.
[0021] [Negative electrode protective film] A preferred example of the negative electrode protective film according to this embodiment will be described.
[0022] The negative electrode protective film according to this embodiment covers at least a part of the negative electrode. The negative electrode protective film contains an alkylene oxide copolymer consisting of a structural unit derived from an alkylene oxide and a structural unit derived from an epoxide having a crosslinkable functional group. The structural unit derived from the alkylene oxide contains a structural unit derived from a propylene oxide, and the structural unit derived from the propylene oxide is contained in an amount of 70.0 mol% or more with respect to the entire alkylene oxide copolymer. The structural unit derived from an epoxide having a crosslinkable functional group is a structural unit derived from at least one selected from the group consisting of allyl glycidyl ether, glycidyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate glycidyl ether, and the structural unit derived from an epoxide having a crosslinkable functional group is contained in an amount of 0.3 mol% or more and 20.0 mol% or less with respect to the entire alkylene oxide copolymer.
[0023] In this specification, "(meth)acrylate" means both acrylate and methacrylate, "(meth)acryloyl" means both acryloyl and methacryloyl, and other similar terms.
[0024] According to the anode protective film of this embodiment, by having the above-mentioned configuration, the generation of dendrites is suppressed, and an anode protective film with improved ion conductivity and Coulomb efficiency is obtained. The Coulomb efficiency is expressed as the ratio of the electric capacity when discharged to the electric capacity when charged. The reason why the ion conductivity and the Coulomb efficiency are improved is not clear, but is thought to be as follows. Since the anode protective film of this embodiment contains an alkylene oxide copolymer, the compatibility with the electrolyte is improved by the skeleton of the main chain of the alkylene oxide copolymer being an ether structure. In particular, since the anode protective film of this embodiment contains 70.0 mol % or more of a structural unit derived from propylene oxide in the skeleton of the alkylene oxide copolymer, this tendency is remarkable. Therefore, when assembling a battery, after the electrolyte is injected, the thin film as the anode protective film swells, and ion conductivity can be expressed. Furthermore, the alkylene oxide copolymer contains 70.0 mol% or more of a propylene oxide-derived structural unit, so that the thin film as the anode protective film can achieve both a high degree of swelling and a high ionic conductivity. The alkylene oxide copolymer contains 0.3 mol% or more of an epoxide-derived structural unit having a crosslinkable functional group, which is a reactive group, as a specific structural unit, and the specific structural unit is used to moderately proceed the crosslinking reaction, so that the thin film as the anode protective film can achieve both a high degree of swelling and a low amount of elution. As a result, it is presumed that the anode protective film according to this embodiment suppresses the generation of dendrites and improves ionic conductivity and Coulombic efficiency. The battery using the anode protective film according to this embodiment suppresses the generation of dendrites and improves ionic conductivity and Coulombic efficiency, so that excellent battery characteristics can be obtained.
[0025] In addition, according to the negative electrode protective film of this embodiment, even if the negative electrode is a lithium negative electrode, it is possible to easily provide a protective layer that covers the negative electrode. Since the negative electrode protective film of this embodiment contains a specific alkylene oxide copolymer having the above-mentioned configuration, regardless of whether the negative electrode is a lithium negative electrode or a negative electrode other than a lithium negative electrode, it is possible to obtain a thin film by film formation in the atmosphere without maintaining a dry environment in all steps. Therefore, when assembling a battery, it is possible to inject an electrolyte after providing a thin film as a protective film on the surface of the negative electrode, so that by using the negative electrode protective film of this embodiment, it is possible to easily provide a protective layer that covers the negative electrode.
[0026] The negative electrode protective film according to this embodiment may contain other components as long as it contains the specific alkylene oxide copolymer, as long as the object of the present invention is not impaired.
[0027] The form of the negative electrode protective film according to this embodiment is not particularly limited. The form of the negative electrode protective film according to this embodiment is preferably a thin film containing an alkylene oxide copolymer, from the viewpoint of easily providing the negative electrode protective film on the negative electrode. The thin film containing an alkylene oxide copolymer is preferably a free-standing film. The free-standing film of the thin film containing an alkylene oxide copolymer refers to a film that can be supported by itself.
[0028] <Alkylene oxide copolymer> The alkylene oxide copolymer contained in the anode protective film according to the present embodiment is composed of a structural unit derived from an alkylene oxide and a structural unit derived from an epoxide having a crosslinkable functional group. The structural unit derived from an alkylene oxide refers to a portion having a chemical structure derived from an alkylene oxide in a copolymer obtained by polymerizing an alkylene oxide monomer as an epoxide monomer and an epoxide monomer having a crosslinkable functional group. The structural unit derived from an epoxide having a crosslinkable functional group refers to a portion having a chemical structure derived from an epoxide having a crosslinkable functional group in the copolymer. In the following description, the structural unit derived from an alkylene oxide may be referred to as "structural unit (A)" and the structural unit derived from an epoxide having a crosslinkable functional group may be referred to as "structural unit (B)".
[0029] The alkylene oxide copolymer may be a random copolymer or a block copolymer. From the viewpoint of ease of synthesis, the alkylene oxide copolymer is preferably a random copolymer.
[0030] The alkylene oxide copolymer is preferably, for example, a copolymer represented by the following general formula (1): The order of the structural units contained in the copolymer represented by the following general formula (1) is not particularly limited.
[0031] [ka]
[0032] In the general formula (1), R 1 is a hydrogen atom or an alkyl group other than a methyl group, and Z 1is any one of the groups represented by the following structural formula (Z-1), the following structural formula (Z-2), the following structural formula (Z-3), the following structural formula (Z-4), or the following structural formula (Z-5), and p, q, and r are, in terms of molar ratio, a number such that, in the copolymer represented by the general formula (1), p is 0 mol % or more and 10 mol % or less, q is a number such that, in terms of molar ratio, 70 mol % or more and 99.7 mol % or less, and r is a number such that, in terms of molar ratio, 0.3 mol % or more and 20.0 mol % or less, and R 1 If there are multiple R 1 are the same or different, and Z 1 If there are multiple Z 1 are the same or different, and in the following structural formula (Z-1), the following structural formula (Z-2), the following structural formula (Z-3), the following structural formula (Z-4), and the following structural formula (Z-5), * represents a bonding position with a methylene group to which any of the following structural formula (Z-1), the following structural formula (Z-2), the following structural formula (Z-3), the following structural formula (Z-4), and the following structural formula (Z-5) is bonded.
[0033] [ka]
[0034] In the general formula (1), R 1 When R is an alkyl group other than a methyl group, 1 The alkyl group other than methyl represented by is preferably an alkyl group having 2 or more and 4 or less carbon atoms.
[0035] The alkylene oxide copolymer contained in the anode protective film according to this embodiment is preferably a copolymer containing, for example, 70.0 mol % or more and 99.7 mol % or less of a structural unit represented by structural formula (A1) described below, 0 mol % or more and 10 mol % or less of at least one structural unit represented by structural formula (A2) described below and structural formula (A3) described below, and 0.3 mol % or more and 20.0 mol % or less of at least one structural unit selected from the group consisting of structural units represented by structural formula (B1) described below, structural formula (B2) described below, structural formula (B3) described below, and structural formula (B4) described below.
[0036] (Structural unit derived from alkylene oxide) The alkylene oxide-derived structural unit (structural unit (A)) is contained in the range of 80.0 mol % or more and 99.7 mol % or less with respect to the entire alkylene oxide copolymer. From the viewpoint of suppressing the generation of dendrites and making it easier to obtain a negative electrode protective film with improved ion conductivity and Coulombic efficiency, the structural unit (A) is preferably contained in an amount of more than 80.0 mol % with respect to the entire alkylene oxide copolymer, more preferably contained in an amount of 81.0 mol % or more, even more preferably contained in an amount of 82.0 mol % or more, even more preferably contained in an amount of 83.0 mol % or more, even more preferably contained in an amount of 84.0 mol % or more, even more preferably contained in an amount of 88.0 mol % or more, and even more preferably contained in an amount of 90.0 mol % or more. From a similar viewpoint, the structural unit (A) is preferably contained in an amount of less than 99.7 mol% based on the entire alkylene oxide copolymer, more preferably 99.5 mol% or less, even more preferably 99.0 mol% or less, even more preferably 98.0 mol% or less, and even more preferably 97.0 mol% or less.
[0037] The structural unit (A) contains a structural unit derived from propylene oxide, and the structural unit derived from propylene oxide is contained in an amount of 70.0 mol% or more relative to the entire alkylene oxide copolymer. From the viewpoint of suppressing the generation of dendrites and making it easier to obtain a negative electrode protective film with improved ion conductivity and Coulombic efficiency, the structural unit derived from propylene oxide is preferably contained in an amount of 75.0 mol% or more relative to the entire alkylene oxide copolymer, more preferably contained in an amount of 80.0 mol% or more, even more preferably contained in an amount of 81.0 mol% or more, even more preferably contained in an amount of 82.0 mol% or more, even more preferably contained in an amount of 83.0 mol% or more, even more preferably contained in an amount of 84.0 mol% or more, even more preferably contained in an amount of 88.0 mol% or more, and even more preferably contained in an amount of 90.0 mol% or more. From a similar viewpoint, the propylene oxide-derived structural unit is preferably contained in an amount of less than 99.7 mol% relative to the entire alkylene oxide copolymer, preferably 99.0 mol% or less, more preferably 98.0 mol% or less, and even more preferably 97.0 mol% or less.
[0038] The structural unit (A) may contain only propylene oxide-derived structural units, or may contain not only propylene oxide-derived structural units but also other alkylene oxide-derived structural units, as long as the structural unit (A) contains propylene oxide-derived structural units in an amount of 70.0 mol% or more relative to the entire alkylene oxide copolymer. The other alkylene oxide-derived structural units may be contained in an amount of 10.0 mol% or less relative to the entire alkylene oxide copolymer. The other alkylene oxide-derived structural units are not particularly limited, and specifically include at least one structural unit of ethylene oxide-derived structural units and butylene oxide-derived structural units. From the viewpoint of suppressing the generation of dendrites and making it easier to obtain an anode protective film with improved ion conductivity and coulombic efficiency, the structural unit (A) is preferably a propylene oxide-derived structural unit.
[0039] The propylene oxide-derived structural unit is preferably a structural unit represented by the following structural formula (A1) from the viewpoint of suppressing the generation of dendrites and more easily obtaining an anode protective film having improved ion conductivity and Coulomb efficiency. The alkylene oxide-derived structural unit may contain only a propylene oxide-derived structural unit represented by the following structural formula (A1), or may contain one or two of an ethylene oxide-derived structural unit represented by the following structural formula (A2) and a butylene oxide-derived structural unit represented by the following structural formula (A3) in addition to the propylene oxide-derived structural unit represented by the following structural formula (A1). From the viewpoint of suppressing the generation of dendrites and more easily obtaining an anode protective film having improved ion conductivity and Coulomb efficiency, the alkylene oxide-derived structural unit preferably contains only a propylene oxide-derived structural unit represented by the following structural formula (A1). When the alkylene oxide-derived structural unit contains only a propylene oxide-derived structural unit represented by the following structural formula (A1), it is more likely that both a high degree of swelling and a high ion conductivity can be achieved.
[0040] [ka]
[0041] (Epoxide-derived structural unit having a crosslinkable functional group) The structural unit (structural unit (B)) derived from an epoxide having a crosslinkable functional group is a structural unit derived from at least one selected from the group consisting of allyl glycidyl ether, glycidyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate glycidyl ether. The reactive groups (allyl group and (meth)acryloyl group) contained in the structural unit derived from an epoxide having a crosslinkable functional group improve adhesion to the surface of the negative electrode. From the viewpoint of suppressing the generation of dendrites and making it easier to obtain a negative electrode protective film having improved ion conductivity and Coulombic efficiency, it is preferable that the structural unit (B) is a structural unit derived from at least one selected from the group consisting of allyl glycidyl ether, glycidyl methacrylate, and 4-hydroxybutyl acrylate glycidyl ether.
[0042] The structural unit (B) is contained in an amount of 0.3 mol% or more and 20.0 mol% or less with respect to the entire alkylene oxide copolymer. If the content ratio of the structural unit (B) is 0.3 mol% or more, the increase in the amount of elution is suppressed and the Coulomb efficiency is easily improved. If the content ratio of the structural unit (B) is 20.0 mol% or less, the crosslink density of the copolymer is not too high, the ratio of the structural unit (A) in the copolymer is high, and the swelling property is easily improved. From the viewpoint of suppressing the generation of dendrites and making it easier to obtain a negative electrode protective film with improved ion conductivity and Coulomb efficiency, the structural unit (B) is preferably contained in an amount of more than 0.3 mol% with respect to the entire alkylene oxide copolymer, more preferably contained in an amount of 0.5 mol% or more, even more preferably contained in an amount of 1.0 mol% or more, even more preferably contained in an amount of 2.0 mol% or more, and even more preferably contained in an amount of 3.0 mol% or more. From a similar viewpoint, the structural unit (B) is preferably contained in an amount of less than 20.0 mol% relative to the entire alkylene oxide copolymer, more preferably contained in an amount of 19.0 mol% or less, even more preferably contained in an amount of 18.0 mol% or less, even more preferably contained in an amount of 17.0 mol% or less, even more preferably contained in an amount of 16.0 mol% or less, even more preferably contained in an amount of 12.0 mol% or less, and even more preferably contained in an amount of 10.0 mol% or less.
[0043] From the viewpoint of suppressing the generation of dendrites and more easily obtaining an anode protective film having improved ion conductivity and Coulombic efficiency, the structural unit (B) is preferably at least one selected from the group consisting of a structural unit represented by the following structural formula (B1), a structural unit represented by the following structural formula (B2), a structural unit represented by the following structural formula (B3), and a structural unit represented by the following structural formula (B4). When the structural unit (B) is one or more of the structural units represented by the following structural formula (B1), the following structural formula (B2), the following structural formula (B3), and the following structural formula (B4), it becomes easier to realize a low amount of elution.
[0044] [ka]
[0045] (Embodiments of alkylene oxide copolymers) From the viewpoint of suppressing the generation of dendrites and making it easier to obtain an anode protective film having improved ion conductivity and Coulombic efficiency, the alkylene oxide copolymer contained in the anode protective film according to this embodiment also preferably contains at least one copolymer selected from the group consisting of a copolymer represented by the following general formula (2), a copolymer represented by the following general formula (3), and a copolymer represented by the following general formula (4):
[0046] In the copolymers represented by the following general formulae (2) to (4), the order of the structural units contained in the copolymers represented by each of these general formulae is not particularly limited.
[0047] [ka]
[0048] In the copolymer represented by the general formula (2), m is a number that is 80.0 mol % or more and 99.7 mol % or less, and n is a number that is 0.3 mol % or more and 20.0 mol % or less, in terms of molar ratio.
[0049] [ka]
[0050] In the copolymer represented by the general formula (3), m and n have the same meanings as m and n in the general formula (2).
[0051] [ka]
[0052] In the copolymer represented by the general formula (4), m and n have the same meanings as m and n in the general formula (2).
[0053] (Method for Producing Alkylene Oxide Copolymer) The method for producing the alkylene oxide copolymer contained in the anode protective film according to the present embodiment is not particularly limited, and can be obtained by a known method. The alkylene oxide copolymer can be obtained, for example, by copolymerizing an alkylene oxide monomer as an epoxide monomer and an epoxide monomer having a crosslinkable functional group. Specifically, the alkylene oxide monomer and the epoxide monomer having a crosslinkable functional group are ring-opened to obtain the desired copolymer. The molar ratio of the constituent unit (A) and the constituent unit (B) in the alkylene oxide copolymer may not match the molar mixture ratio of the alkylene oxide monomer as the starting material of the constituent unit (A) and the epoxide monomer having a crosslinkable functional group as the starting material of the constituent unit (B) due to differences in reactivity. The polymerization catalyst and polymerization solvent may be appropriately selected so that the desired copolymer can be obtained. The polymerization catalyst is not particularly limited, and examples thereof include an alkali catalyst, a porphyrin catalyst, and a composite metal cyanide complex catalyst. The polymerization solvent is not particularly limited, and examples thereof include aliphatic hydrocarbons, aromatic hydrocarbons, halogenated hydrocarbons, alcohols, ketones, esters, and ethers.
[0054] <Characteristics of the negative electrode protective film> In the negative electrode protective film according to this embodiment, the amount of the alkylene oxide copolymer eluted in ethyl acetate is preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, and particularly preferably 10% or less. Since the low molecular weight components of the eluted alkylene oxide copolymer become irreversible capacity, it is preferable that the amount of elution is as low as possible. The lower limit of the amount of elution of the alkylene oxide copolymer is not particularly limited, and may be, for example, 1% or more, 0.1% or more, or 0%.
[0055] In the negative electrode protective film according to this embodiment, it is preferable that the amount of elution of the alkylene oxide copolymer in ethyl acetate is within the above range, and the swelling degree of the alkylene oxide copolymer in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 50% or more and 200% or less. It is more preferable that the amount of elution is within the above range, and the swelling degree is 52% or more and 180% or less, it is even more preferable that the amount of elution is within the above range, and the swelling degree is 60% or more and 160% or less, and it is even more preferable that the amount of elution is within the above range, and the swelling degree is 70% or more and 145% or less.
[0056] When a thin film made using an alkylene oxide copolymer is used in, for example, a lithium ion secondary battery, the thin film containing the alkylene oxide copolymer does not contain lithium ions before injecting an electrolyte solution containing lithium ions, and therefore does not exhibit ionic conductivity. When an electrolyte solution containing lithium ions, etc. is injected into a thin film containing an alkylene oxide copolymer, the thin film containing the alkylene oxide copolymer swells. The thin film swollen by the electrolyte exhibits ionic conductivity. For this reason, in the anode protective film according to this embodiment, the anode protective film preferably further contains an electrolyte solution in addition to the thin film containing an alkylene oxide copolymer. In order to improve the performance of a battery using a thin film containing an alkylene oxide copolymer as the anode protective film, it is preferable that the ionic conductivity of the thin film is high. From this viewpoint, it is preferable that the anode protective film according to this embodiment has high swelling property in the above electrolyte solution and carbonate-based solvents used as a solvent for the electrolyte solution. For example, if the degree of swelling in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 50% or more and 150% or less, the ion conductivity is improved, and the battery performance is likely to be improved.
[0057] When an electrolyte solution is contained in a thin film containing an alkylene oxide copolymer, the electrolyte solution preferably contains a carbonate-based solvent and a lithium salt, and the molar ratio of the lithium salt to the carbonate-based solvent (the lithium salt / the carbonate-based solvent) is 1 / 6 or more and 1 / 1 or less. An electrolyte solution having a concentration in which the molar ratio of the lithium salt to the carbonate-based solvent is 1 / 6 or more and 1 / 1 or less has a higher concentration than that of a general electrolyte solution. By using the electrolyte solution, the dissolution and deposition of lithium is made uniform, and the effect of suppressing the generation of dendrites is easily improved.
[0058] From the viewpoint of film strength, the thickness of the anode protective film according to the present embodiment is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more. From the viewpoint of reducing the resistance of the film, the thickness of the anode protective film according to the present embodiment is preferably 20 μm or less, more preferably 16 μm or less, and even more preferably 12 μm or less.
[0059] <Method of manufacturing the negative electrode protective film> In the anode protective film according to the present embodiment, a photopolymerization initiator is preferably used from the viewpoint of facilitating the production of a thin film (i.e., a thin film containing an alkylene oxide copolymer) as the anode protective film. When a photopolymerization initiator is used in the anode protective film according to the present embodiment, reactive groups (allyl groups and (meth)acryloyl groups) in the side chains of the alkylene oxide copolymer in the thin film react to crosslink the thin film containing the alkylene oxide copolymer.
[0060] An example of a preferred method for producing the negative electrode protective film according to this embodiment will be described.
[0061] The method for producing the anode protective film according to this embodiment includes the following steps. A step of mixing an alkylene oxide copolymer and a photopolymerization initiator to prepare a mixture (step 1). A step of forming the mixture to obtain a formed product (step 2). A step (step 3) of irradiating the molded product with energy rays to obtain a negative electrode protective film containing an alkylene oxide copolymer. "Energy rays" refers to radiation having an energy quantum among electromagnetic waves or charged particle beams. Examples of energy rays include ultraviolet rays, radiation, and electron beams. Ultraviolet rays can be irradiated using electrodeless lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, black lights, LED lamps, and the like. Electron beams can be irradiated using electrons generated by electron beam accelerators, and the like.
[0062] According to one aspect of the method for producing the anode protective film according to the present embodiment, a thin film containing an alkylene oxide copolymer as the anode protective film is obtained, and the thin film is easily obtained as a free-standing film. Therefore, regardless of whether the anode is a lithium anode or an anode other than a lithium anode, it is possible to form the anode protective film on the surface of the anode without maintaining a dry environment in all steps. Then, by using the anode protective film according to the present embodiment, it is possible to provide a protective layer that covers the anode in a simple process, and further, a battery according to the present embodiment can be obtained in a simple process.
[0063] (Process 1) Step 1 is a step of mixing raw materials for obtaining the negative electrode protective film to obtain a mixture. In step 1, first, the above-mentioned alkylene oxide copolymer and photopolymerization initiator are prepared as raw materials for obtaining the negative electrode protective film. The alkylene oxide copolymer is obtained, for example, by the above-mentioned manufacturing method. Next, the desired amount of these prepared raw materials is weighed. Thereafter, the weighed raw materials are mixed, and further, a dilution solvent is added as necessary, to prepare a mixture. The mixture may be prepared by stirring the raw materials with a known stirring device or the like. The mixture prepared in step 1 is a mixture for forming the negative electrode protective film.
[0064] The photopolymerization initiator is not particularly limited, and may be a known compound. The photopolymerization initiator is preferably a photopolymerization initiator that is sensitive to ultraviolet light. The photopolymerization initiator may be used alone or in combination of two or more kinds.
[0065] Specific examples of the photopolymerization initiator include α-ketol compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and 1-hydroxycyclohexylphenyl ketone; acetophenone compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1; benzoin ether compounds such as benzoin ethyl ether, benzoin isopropyl ether, and anisoin methyl ether; ketal compounds such as benzyl dimethyl ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenone-1,1-propanedione-2-(o-ethoxycarbonyl)oxime; benzophenone compounds such as benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, and 2-methylthioxanthone; camphorquinone, halogenated ketones, acylphosphinoxides, acylphosphonates, and oligo[2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propanone].
[0066] The content of the photopolymerization initiator is, for example, preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.5 parts by mass or more and 7.5 parts by mass or less, and even more preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the alkylene oxide copolymer.
[0067] (Process 2) Step 2 is a step of obtaining a molded product from the mixture prepared in step 1. In step 2, the mixture prepared in step 1 is molded to obtain a molded product. The molding of the mixture is not particularly limited, and may be molded, for example, by applying the mixture to the surface of a support to form a coating film. As the support, for example, a release film having a release-treated surface on at least one side of the substrate may be used. The mixture prepared in step 1 may be applied to the release-treated surface of the release film to form a coating film to obtain a molded product. In addition, when a release film is used, a first release film having a release-treated surface on at least one side of the substrate is used, and the mixture prepared in step 1 is applied to the release-treated surface to form a coating film to obtain a molded product, and then the release-treated surface of a second release film having a release-treated surface on at least one side of the substrate may be superimposed on the molded product. The molded product may be sandwiched between the first release film and the second release film and subjected to step 3.
[0068] (Step 3) Step 3 is a step of obtaining a negative electrode protective film containing an alkylene oxide copolymer from the molded product obtained in step 2. In step 3, the molded product molded in step 2 is irradiated with energy rays, whereby the alkylene oxide copolymer is crosslinked to obtain a thin film containing a crosslinked product of the alkylene oxide copolymer. The type of energy rays is not particularly limited, and is preferably ultraviolet rays from the viewpoints of reactivity and workability. The device for irradiating the molded product with ultraviolet rays is not particularly limited, and may be, for example, a device equipped with an ultraviolet LED lamp, a device equipped with a high-pressure mercury lamp, or a device equipped with a metal halide lamp.
[0069] The conditions for irradiating the molded product with ultraviolet light are not particularly limited. The maximum illuminance and the integrated light quantity when irradiating the molded product with ultraviolet light are, for example, as follows: Maximum illuminance: 5 mW / cm 2 More than 1000mW / cm 2 The integrated light quantity is preferably 50 mJ / cm or less. 2 More than 5000mJ / cm 2 It is preferable that:
[0070] The anode protective film according to the present embodiment is obtained through the above steps 1, 2, and 3. The release film used as the support in step 2 is irradiated with ultraviolet light in step 3, and then attached to a thin film containing a crosslinked product of an alkylene oxide copolymer as the anode protective film until the anode protective film according to the present embodiment is used. The release film is peeled off from the thin film, and the anode protective film according to the present embodiment is used.
[0071] <How to use the negative electrode protective film> The negative electrode protective film according to this embodiment is used to cover at least a part of the negative electrode. The material of the negative electrode is not particularly limited, and examples thereof include lithium metal, lithium alloy, metal oxide, metal sulfide, metal nitride, and graphite. Among these, the negative electrode is preferably a lithium negative electrode containing at least one of lithium metal and lithium alloy. If the negative electrode is a lithium negative electrode, a battery with a high energy density can be easily obtained.
[0072] The lithium negative electrode is not particularly limited, and may be any negative electrode having a portion having a metal containing lithium such as lithium metal and lithium alloy, etc. Specific examples of the lithium negative electrode include lithium metal foil, lithium alloy foil, lithium metal film or lithium alloy film deposited on a negative electrode current collector, and lithium metal film or lithium alloy film deposited on a resin film.
[0073] The negative electrode protective film according to the present embodiment is provided, for example, on the surface of the lithium negative electrode on the electrolyte layer side, and is provided at the interface between the lithium negative electrode and the electrolyte solution. In this case, the negative electrode protective film may cover a part of the surface of the lithium negative electrode on the electrolyte layer side, or may cover the entire surface. The negative electrode protective film according to the present embodiment is provided at the interface between the lithium negative electrode and the electrolyte solution, which makes it easier to suppress the generation of dendrites and further suppress their growth.
[0074] Here, an example of a state in which a negative electrode is covered with the negative electrode protective film according to the present embodiment in order to protect the negative electrode will be described with reference to the drawings. In the drawings, some parts are illustrated enlarged or reduced in size for ease of explanation.
[0075] FIG. 1 shows a cross-sectional view of a negative electrode 10 with a negative electrode protective film in which a negative electrode 13 is protected. The negative electrode 10 with a negative electrode protective film is an example of a state in which a negative electrode protective film 11 according to the present embodiment is provided on the surface of the negative electrode 13. The negative electrode 10 with a negative electrode protective film shown in FIG. 1 includes a negative electrode 13 and a negative electrode protective film 11 that covers the negative electrode 13. In the negative electrode 10 with a negative electrode protective film shown in FIG. 1, a lithium negative electrode is used as the negative electrode 13. The negative electrode 13 is made of, for example, a lithium metal foil. The negative electrode 13 has a first main surface 131 of the negative electrode 13 and a second main surface 132 of the negative electrode 13 that is the surface opposite to the first main surface 131, and the negative electrode protective film 11 has a first main surface 111 of the negative electrode protective film 11 and a second main surface 112 that is the surface opposite to the first main surface 111. In the negative electrode 10 with the negative electrode protective film, the negative electrode protective film 11 is provided on the first main surface 131 of the negative electrode 13 so that the first main surface 131 of the negative electrode 13 and the second main surface 112 of the negative electrode protective film 11 are in direct contact with each other. The negative electrode 10 with the negative electrode protective film is provided with the negative electrode protective film 11 on the entire surface of the first main surface 131 of the negative electrode 13. The second main surface 132 of the negative electrode 13 is the surface on the side on which a negative electrode current collector (not shown) is provided. The first main surface 111 of the negative electrode protective film 11 is the surface on the side on which an electrolyte layer (not shown) is provided. The negative electrode 10 with the negative electrode protective film is obtained by attaching a thin film as the negative electrode protective film 11 to the negative electrode 13. By covering the surface of the negative electrode 13 with the negative electrode protective film 11, the generation of dendrites is suppressed and the ionic conductivity and Coulombic efficiency are improved. Here, the main surface refers to the largest surface of the negative electrode protective film 11 and the negative electrode 13, and indicates the surface facing the thickness direction (that is, the lamination direction of the negative electrode protective film 11 and the negative electrode 13).
[0076] Although the negative electrode with the negative electrode protective film has been described above as an example of a state in which the negative electrode is protected by the negative electrode protective film according to the present embodiment with reference to Fig. 1, the example of protecting the negative electrode by the negative electrode protective film according to the present embodiment is not limited to this. The negative electrode protective film according to the present embodiment may adopt various forms as long as it can protect the negative electrode and can obtain the effects of the negative electrode protective film according to the present embodiment.
[0077] [battery] Next, a preferred example of the battery according to this embodiment will be described.
[0078] The battery according to the present embodiment includes the anode protective film according to the present embodiment. In the present embodiment, it is preferable that the battery includes the anode protective film according to the present embodiment as a constituent material of the battery. The battery is composed of a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode. By adopting such a configuration, a battery having excellent characteristics can be obtained. In addition, the battery is preferably a secondary battery, and more preferably a lithium ion secondary battery. The structure of the battery according to the present embodiment is not particularly limited, and may be a stacked structure or a wound structure.
[0079] Here, an example of a battery using the anode protective film according to the present embodiment will be described with reference to the drawings. In the drawings, some parts are illustrated enlarged or reduced in size for ease of explanation.
[0080] FIG. 2 shows an example of a battery using the anode protective film according to the present embodiment. The battery 100 shown in FIG. 2 is a lithium ion secondary battery. As shown in FIG. 2, the battery 100 has a structure in which a cathode layer 20 is laminated on a cathode current collector 25 as a cathode side, and has a structure in which an anode 10 with an anode protective film is laminated on an anode current collector 15 as a cathode side. The anode 10 with an anode protective film shown in FIG. 1 is used as the anode 10 with an anode protective film, and one surface of the anode 13 is covered with an anode protective film 11. The battery 100 has an electrolyte layer 30 between the cathode layer 20 and the anode protective film 11. The electrolyte layer 30 is composed of an electrolyte 33 and a separator 31 impregnated with the electrolyte 33, and the separator 31 separates the cathode side from the anode side. The negative electrode protective film 11 contains the electrolyte solution 33 of the electrolyte layer 30, and is swollen by the electrolyte solution 33. The battery 100 has a laminated structure in which a positive electrode current collector 25, a positive electrode layer 20, an electrolyte layer 30, a negative electrode protective film 11, a negative electrode 13, and a negative electrode current collector 15 are laminated in this order from the positive electrode current collector 25 toward the negative electrode current collector 15, and the laminated structure is contained inside a container (not shown).
[0081] Although an example of a battery using the anode protective film according to the present embodiment has been described above with reference to Fig. 2, the example of the battery using the anode protective film according to the present embodiment is not limited to this. The battery according to the present embodiment may adopt various forms as long as the anode can be protected using the anode protective film according to the present embodiment and the effect of using the anode protective film according to the present embodiment can be obtained.
[0082] In the case where the battery according to the present embodiment is a lithium ion secondary battery, as long as the battery is provided with the negative electrode protective film according to the present embodiment, the various components of the lithium ion secondary battery are not particularly limited, and for example, materials that are generally used for such batteries can be used.
[0083] Examples of materials used for the positive electrode current collector and the negative electrode current collector include metal foils or metal plates such as copper, aluminum, nickel, titanium, and stainless steel, as well as carbon sheets and carbon nanotube sheets.
[0084] The positive electrode layer is composed of, for example, a positive electrode active material such as a lithium-containing composite oxide, a conductive assistant such as a carbon-based material, a binder, and the like.
[0085] The electrolyte layer is composed of, for example, an electrolytic solution and a separator. When a separator is used, the material of the separator is not particularly limited, and examples thereof include a porous resin sheet containing a resin such as polyolefin, polyester, or polyamide.
[0086] In the battery according to the present embodiment, the electrolyte preferably contains a lithium salt and a carbonate-based solvent. In order to easily improve the effect of suppressing the generation of dendrites, the molar ratio of the lithium salt to the carbonate-based solvent (the lithium salt / the carbonate-based solvent) is preferably 1 / 6 or more and 1 / 1 or less. This molar ratio is more preferably 1 / 4 or more and 1 / 1 or less, and even more preferably 1 / 3 or more and 1 / 1 or less.
[0087] Specific examples of lithium salts include lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium 2-trifluoromethyl-4,5-dicyanoimidazolate, lithium 4,5-dicyano-1,2,3-triazolate, lithium bis(pentafluoroethylsulfonyl)imide, lithium borofluoride, lithium bis(oxalato)borate, lithium nitrate, lithium chloride, lithium bromide, and lithium fluoride. The lithium salt may be one or more of these exemplified lithium salts.
[0088] Specific examples of carbonate-based solvents include dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, propylene carbonate, and butylene carbonate. The carbonate-based solvent may be one or more of these lithium salts. Here, the carbonate-based solvent in this embodiment refers to a compound having a carbonate skeleton in its molecular structure.
[0089] The negative electrode and the negative electrode protective film are as described above. The negative electrode protective film is the negative electrode protective film according to this embodiment.
[0090] The present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES
[0091] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples in any way.
[0092] Measurements and evaluations in the following Examples and Comparative Examples were carried out by the methods described below.
[0093] [Measurement of elution amount] The thin film obtained in each of the examples and comparative examples described below was weighed to about 300 mg. The mass of the thin film at this time was defined as M0. The thin film was wrapped in a polyester mesh (mesh size 200). The mass of the thin film wrapped in the polyester mesh was weighed, and the mass of the thin film was subtracted to calculate the mass of the polyester mesh alone. Next, the thin film wrapped in the polyester mesh was immersed in ethyl acetate at 23°C for 48 hours. Thereafter, the thin film wrapped in the polyester mesh was taken out of the ethyl acetate, dried in an oven at 120°C for 2 hours, and further air-dried for 2 hours in an environment at a temperature of 23°C and a relative humidity of 50%. The mass after the air drying was weighed, and the mass of the thin film alone after immersion was calculated by subtracting the mass of the polyester mesh alone. The mass at this time was defined as M1. The amount of elution was calculated using the following formula (F1). Elution amount (%)={(M0-M1) / M0}×100 (F1) In formula (F1), M0 represents the mass of the thin film weighed before being wrapped in the polyester mesh, and M1 represents the mass of the thin film alone after being immersed in ethyl acetate.
[0094] [Swelling degree measurement] The thin film obtained in each of the examples and comparative examples described below was cut to about 3 cm (vertical) x about 3 cm (horizontal), and the obtained thin film piece was weighed to be about 1 g. The mass at this time was defined as W0. The thin film piece was wrapped in a polyester mesh (mesh size 200), and the mass of the thin film piece wrapped in the polyester mesh was weighed, and the mass of the thin film piece was subtracted to calculate the mass of the polyester mesh alone. The thin film was immersed in a carbonate-based solvent [composition: mixed solvent of ethylene carbonate / dimethyl carbonate = 1 / 1 (volume ratio)] for 24 hours to cause swelling. Thereafter, the thin film piece wrapped in the polyester mesh was pulled out, the solvent on the surface was wiped with a paper wiper, and the mass was measured, and the mass of the swollen thin film piece was calculated by subtracting the mass of the polyester mesh alone. The mass at this time was defined as W1. The swelling degree was calculated using the following formula (F2). Swelling degree (%) = {(W1-W0) / W0} × 100 (F2) In formula (F2), W0 represents the mass of the thin film piece weighed before being wrapped in the polyester mesh, and W1 represents the mass of only the thin film piece after swelling.
[0095] [Ionic conductivity measurement] The lithium half-cells obtained in each of the Examples and Comparative Examples described below were measured using the AC impedance method, which applies an AC voltage (applied voltage of 10 mV) between the electrodes to measure the resistance component. The ionic conductivity was calculated from the real impedance intercept of the obtained Cole-Cole plot. A potentiostat / galvanostat (VMP-300, manufactured by Biologic) was used for the measurements. Ionic conductivity (σ A ) was calculated using the following formula (F3). σ A =L A / (R A ×S A ) (F3) In formula (F3), σ A is the ionic conductivity (unit: S cm -1 ), R A is resistance (unit: Ω), S A is the cross-sectional area (unit: cm) of the thin-film lithium half-cell at the time of measurement 2 ), L A indicates the distance between electrodes (unit: cm). The measurement temperature was 25°C. The ionic conductivity (σ A ) was calculated.
[0096] [Coulombic efficiency measurement] The lithium half-cells obtained in each of the examples and comparative examples described below were discharged for 1 hour at a constant current of 0.1C at a temperature of 25°C, and then charged to a cell voltage of 1.0V at a constant current of 0.1C at a temperature of 25°C. This discharge and charge operation was counted as one cycle, and this operation was repeated two more times for a total of three cycles. The discharge capacity at the third cycle was C0, the charge capacity at the third cycle was C1, and the coulombic efficiency was calculated from the following formula (F4). A potentiostat / galvanostat (VMP-300, manufactured by Biologic) was used for the measurement. Coulomb efficiency (%) = C1 / C0 × 100 (F4) In formula (F4), C0 represents the discharge capacity in the third cycle, and C1 represents the charge capacity in the third cycle.
[0097] The closer the Coulombic efficiency is to 100%, the better the battery performance is, and therefore the better the performance of the anode protective film is. On the other hand, if the Coulombic efficiency exceeds 100%, it is highly likely that dendrites have grown and caused a micro-short circuit, indicating that the performance of the film to uniformly dissolve and deposit lithium is poor.
[0098] [Example 1] (Synthesis of Polymerization Catalyst) A potassium hexacyanocobaltate(III) solution was prepared by dissolving 1.33 g of potassium hexacyanocobaltate(III) (K3[Co(CN)6], Fujifilm Wako Pure Chemical Industries, Ltd.) in 20 mL of deionized water. A ZnCl2 solution was prepared by dissolving 11.42 g of ZnCl2 in a mixed solution of 60 mL of deionized water and 30 mL of t-butyl alcohol. The potassium hexacyanocobaltate(III) solution was then added dropwise to the vigorously stirred ZnCl2 solution at 50°C over 45 minutes, and the mixture was then vigorously stirred for 60 minutes to obtain a white suspension. The resulting white suspension was centrifuged at 5000 rpm to isolate a white solid. The isolated white solid was resuspended in a solution of t-butyl alcohol and deionized water (volume ratio, t-butyl alcohol:deionized water = 5:5) with vigorously stirring for 30 minutes. Then, the amount of t-butyl alcohol was gradually increased relative to the water (the volume ratio of t-butyl alcohol:deionized water was changed from 6:4 to 7:3, 8:2, and 9:1), and the separation and resuspension by centrifugation were repeated several times. Finally, the white solid was resuspended in t-butyl alcohol and then separated by centrifugation. Then, the solid was dried under vacuum at 50°C until it reached a predetermined mass, thereby obtaining Zn3(Co[CN]6)2 as a double metal cyanide complex catalyst (hereinafter referred to as DMC catalyst (DMC catalyst: Double Metal Cyanide Complex catalyst)).
[0099] (Synthesis of Copolymer A) Propylene oxide was prepared as an alkylene oxide monomer, and allyl glycidyl ether was prepared as an epoxide monomer having a crosslinkable functional group. Propylene oxide and allyl glycidyl ether were mixed to a molar ratio of 97:3. 1 mg of the DMC catalyst synthesized above was added to 10 mL of the mixed monomer mixture, and 200 ppm of phenothiazine was further added. After that, the mixture was stirred at room temperature for 40 hours to carry out a polymerization reaction, and copolymer A was obtained.
[0100] The structure of the obtained copolymer A was confirmed by nuclear magnetic resonance spectroscopy ( 1 When confirmed by H-NMR (Biospin Avance 500, Bruker) using d-chloroform (CDCl3, containing 0.03% by mass of tetramethylsilane) as a solvent, the molar ratio of the alkylene oxide-derived structural unit (structural unit (A)) in copolymer A to the epoxide-derived structural unit (structural unit (B)) having a crosslinkable functional group was structural unit (A):structural unit (B)=98:2 (see FIG. 3A). In copolymer A, structural unit (A) is a structural unit represented by the above-mentioned structural formula (A1), and structural unit (B) is a structural unit represented by the above-mentioned structural formula (B1).
[0101] (Preparation of thin films) To the obtained copolymer A, 3% by mass of a photopolymerization initiator (manufactured by IGM Resins BV, product name "Omnirad 184") was added (copolymer: initiator = 97: 3% by mass), and further diluted with ethyl acetate and stirred to prepare a solution for thin film formation with a solid content concentration of 30% by mass. A first release film (manufactured by Lintec Corporation, product name "SP-PET381031") was prepared, and the prepared solution for thin film formation was applied to the release-treated surface of this release film, and dried at 120 ° C for 1 minute to form a thin film layer with a thickness of 10 μm. Furthermore, a second release film (manufactured by Lintec Corporation, product name "SP-PET382150") was prepared, and the release-treated surface of this release film was attached to the surface of the thin film layer. Thereafter, the thin film laminate sandwiched between the first release film and the second release film was placed on a stainless steel plate and heated to 50 ° C, and irradiated with ultraviolet light [illuminance: 200 mW / cm 2 , Accumulated light intensity: 1000mJ / cm 2 The amount of elution and the degree of swelling of the obtained thin film were measured using an illuminance actinometer (control unit: EYE UV METER UVPF-A2, light receiving unit: EYE UV METER PD-365A2) manufactured by Eye Graphics Co., Ltd. The obtained thin film was a negative electrode protective film. The amount of elution and the degree of swelling of the obtained thin film were measured using the above-mentioned method.
[0102] (Fabrication of lithium half-cells) The thin film prepared above was attached to a lithium metal foil having a thickness of about 400 μm as a negative electrode protective film, and punched to a diameter of 16 mm to prepare a lithium negative electrode with a negative electrode protective film. Furthermore, a Tetron mesh having a diameter of 19 mm and a thickness of 61 μm (UX-screen 150-035 / 380PW, manufactured by NBC Meshtec Co., Ltd.) was placed on the thin film (the surface opposite to the lithium metal foil), and a copper foil having a thickness of 12 μm and a diameter of 16 mm was placed on the Tetron mesh (the surface opposite to the thin film) to prepare a lithium half cell. An electrolyte was poured into the prepared cell, and the cell was allowed to stand at 25° C. for 18 hours, after which the ionic conductivity and Coulombic efficiency were measured by the above-mentioned measurement method. This electrolyte was an electrolyte obtained by mixing lithium bis(fluorosulfonyl)imide and dimethyl carbonate in a molar ratio of 1:2.
[0103] [Example 2] (Polymerization of Copolymer B) Polymerization was carried out in the same manner as in Example 1, except that propylene oxide and allyl glycidyl ether were mixed in a molar ratio of 90:10, to obtain copolymer B. The obtained copolymer B was polymerized in the same manner as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1 (see Figure 3B).
[0104] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that Copolymer B was used.
[0105] (Fabrication of lithium half-cells) A lithium half-cell was produced in the same manner as in Example 1, except that the thin film obtained using copolymer B was used.
[0106] [Example 3] (Polymerization of Copolymer C) Glycidyl methacrylate was prepared as an epoxide monomer having a crosslinkable functional group. Propylene oxide and glycidyl methacrylate were mixed to a molar ratio of 97:3. 0.1 mg of the DMC catalyst synthesized above was added to 10 mL of the mixed monomers. Furthermore, 200 ppm of phenothiazine was added, and ethyl acetate was added so that the mass ratio of ethyl acetate to the mixed monomers was 50:50. Thereafter, the mixture was stirred at 60°C for 24 hours to carry out a polymerization reaction, thereby obtaining copolymer C. The obtained copolymer C was subjected to the same procedure as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1 (see Figure 3C).
[0107] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that Copolymer C was used.
[0108] (Fabrication of lithium half-cells) A lithium half-cell was produced in the same manner as in Example 1, except that a thin film obtained using copolymer C was used.
[0109] [Example 4] (Polymerization of Copolymer D) Polymerization was carried out in the same manner as in Example 3, except that propylene oxide and glycidyl methacrylate were mixed in a molar ratio of 90:10, to obtain copolymer D. The obtained copolymer D was polymerized in the same manner as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1 (see Figure 3D).
[0110] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that Copolymer D was used.
[0111] (Fabrication of lithium half-cells) A lithium half-cell was prepared in the same manner as in Example 1, except that the thin film obtained using copolymer D was used.
[0112] [Example 5] (Polymerization of Copolymer E) Polymerization was carried out in the same manner as in Example 3, except that propylene oxide and glycidyl methacrylate were mixed in a molar ratio of 80:20, to obtain copolymer E. The obtained copolymer E was polymerized in the same manner as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1 (see Figure 3E).
[0113] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that copolymer E was used.
[0114] (Fabrication of lithium half-cells) A lithium half-cell was produced in the same manner as in Example 1, except that the thin film obtained using copolymer E was used.
[0115] [Example 6] (Polymerization of Copolymer F) As an epoxide monomer having a crosslinkable functional group, 4-hydroxybutyl acrylate glycidyl ether was prepared. Polymerization was carried out in the same manner as in Example 3, except that propylene oxide and 4-hydroxybutyl acrylate glycidyl ether were mixed in a molar ratio of 97:3, to obtain copolymer F. The obtained copolymer F was subjected to polymerization in the same manner as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1 (see FIG. 3F).
[0116] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that copolymer F was used.
[0117] (Fabrication of lithium half-cells) A lithium half-cell was produced in the same manner as in Example 1, except that the thin film obtained using copolymer F was used.
[0118] [Example 7] (Polymerization of Copolymer G) Polymerization was carried out in the same manner as in Example 6, except that propylene oxide and 4-hydroxybutyl acrylate glycidyl ether were mixed as the epoxide monomers in a molar ratio of 90:10, to obtain copolymer G. The obtained copolymer G was subjected to polymerization in the same manner as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1 (see Figure 3G).
[0119] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that copolymer G was used.
[0120] (Fabrication of lithium half-cells) A lithium half-cell was prepared in the same manner as in Example 1, except that the thin film obtained using copolymer G was used.
[0121] [Comparative Example 1] (Fabrication of lithium half-cells) A lithium half-cell was produced in the same manner as in Example 1, except that no thin film was used as the negative electrode protective film. That is, a lithium negative electrode was produced by punching out a lithium metal foil having a thickness of about 400 μm to a diameter of 16 mm, a Tetron mesh having a diameter of 19 mm and a thickness of 61 μm (UX-screen 150-035 / 380PW, manufactured by NBC Meshtec Co., Ltd.) was placed on this lithium negative electrode, and a copper foil having a thickness of 12 μm and a diameter of 16 mm was placed on the Tetron mesh (the surface opposite to the lithium negative electrode side) to produce a lithium half-cell. A lithium half-cell was produced in the same manner as in Example 1, except that no thin film was used as the negative electrode protective film.
[0122] [Comparative Example 2] (Polymerization of homopolymer A) Polymerization was carried out in the same manner as in Example 1, except that only propylene oxide was used as the epoxide monomer, to obtain a homopolymer A. The structure of the obtained homopolymer A was determined in the same manner as in Example 1, 1When confirmed by H-NMR, homopolymer A was a homopolymer consisting only of structural unit (A). The structural unit (A) in homopolymer A is a structural unit represented by the above-mentioned structural formula (A1).
[0123] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that homopolymer A was used.
[0124] (Fabrication of lithium half-cells) A lithium half-cell was prepared in the same manner as in Example 1, except that the thin film obtained using homopolymer A was used.
[0125] [Comparative Example 3] (Polymerization of Copolymer H) Polymerization was carried out in the same manner as in Example 3, except that propylene oxide and glycidyl methacrylate were mixed as epoxide monomers in a molar ratio of 70:30, to obtain copolymer H. The obtained copolymer H was subjected to polymerization in the same manner as in Example 1. 1 The structures confirmed by H-NMR are shown in Table 1.
[0126] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that copolymer H was used.
[0127] (Fabrication of lithium half-cells) An attempt was made to prepare a lithium half-cell in the same manner as in Example 1, except that a thin film obtained using copolymer H was used. However, the film was brittle and could not be placed on the lithium negative electrode. For this reason, in Comparative Example 3, the battery characteristics could not be evaluated.
[0128] [Table 1]
[0129] [Table 2]
[0130] The results shown in Table 2 show that the ionic conductivity and Coulombic efficiency can be improved by the anode protective films obtained in Examples 1 to 7. It is also inferred from these results that the anode protective films obtained in Examples 1 to 7 can suppress the generation of dendrites. [Explanation of symbols]
[0131] 10...negative electrode with negative electrode protective film, 11...negative electrode protective film, 13...negative electrode, 15...negative electrode current collector, 20...positive electrode layer, 25...positive electrode current collector, 30...electrolyte layer, 31...separator, 33...electrolyte, 100...battery, 111...first main surface of negative electrode protective film, 112...second main surface of negative electrode protective film, 131...first main surface of negative electrode, 132...second main surface of negative electrode.
Claims
1. A negative electrode protective film that covers at least a part of the negative electrode, The present invention includes an alkylene oxide copolymer including a structural unit derived from an alkylene oxide and a structural unit derived from an epoxide having a crosslinkable functional group, The alkylene oxide-derived structural unit includes a propylene oxide-derived structural unit, The alkylene oxide copolymer contains 70.0 mol % or more of the propylene oxide-derived structural unit relative to the entire alkylene oxide copolymer, the epoxide-derived structural unit having a crosslinkable functional group is a structural unit derived from at least one selected from the group consisting of allyl glycidyl ether, glycidyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate glycidyl ether, and is contained in an amount of 0.3 mol % or more and 20.0 mol % or less with respect to the entire alkylene oxide copolymer; Negative electrode protective film.
2. The anode protective film according to claim 1 , the alkylene oxide-derived structural unit is the propylene oxide-derived structural unit, The propylene oxide-derived structural unit is a structural unit represented by the following structural formula (A1): The epoxide-derived structural unit having a crosslinkable functional group is at least one structural unit selected from the group consisting of structural units represented by the following structural formula (B1), structural formula (B2), structural formula (B3), and structural formula (B4): Negative electrode protective film. 【Chemistry 1】 【Chemistry 2】
3. The anode protective film according to claim 1 or 2, the amount of the alkylene oxide copolymer eluted in ethyl acetate is 10% or less; the degree of swelling of the alkylene oxide copolymer in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 50% or more and 200% or less; Negative electrode protective film.
4. The anode protective film according to claim 1 or 2, the negative electrode protective film further contains an electrolyte, the electrolyte solution contains a carbonate-based solvent and a lithium salt; a molar ratio of the lithium salt to the carbonate-based solvent (lithium salt / carbonate-based solvent) is 1 / 6 or more and 1 / 1 or less; Negative electrode protective film.
5. The anode protective film according to claim 1 or 2, The negative electrode is a lithium negative electrode. Negative electrode protective film.
6. The negative electrode protective film according to claim 1 or 2, battery.
Citation Information
Patent Citations
Lithium metal battery
JP2016219411A
Binder composition for lithium-ion secondary battery electrode, slurry composition for lithium-ion secondary battery electrode, lithium-ion secondary battery electrode and lithium-ion secondary battery
JP2020123590A